Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1007/bf02024736
|View full text |Cite
|
Sign up to set email alerts
|

Anti-arthritic effect of bee venom

Abstract: Bee venom, administered subcutaneously, suppressed the development of carrageenan-induced paw edema and adjuvant arthritis in the rat in a dose-related manner. A single dose of bee venom administered subcutaneously the day before or on the day of injection of complete Freund's adjuvant (CFA) effectively suppressed the development of polyarthritis. This suppressive effect decreased progressively as dosing was delayed. Bee venom was found to be most effective when mixed and injected (sub-plantar) together with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Based on these inferences, we could justify both our own and other results showing that BV does not have an effect on established arthritis (Hadjipetrou-Kourounakis and Yiangou, 1988;Chang and Bliven, 1979). The contribution of GCs to BV action has been confirmed by a study showing that melittin produces an increase in GC levels that is correlated with their antiarthritic effects (Dunn and Killion, 1988).…”
Section: Discussionsupporting
confidence: 58%
“…Based on these inferences, we could justify both our own and other results showing that BV does not have an effect on established arthritis (Hadjipetrou-Kourounakis and Yiangou, 1988;Chang and Bliven, 1979). The contribution of GCs to BV action has been confirmed by a study showing that melittin produces an increase in GC levels that is correlated with their antiarthritic effects (Dunn and Killion, 1988).…”
Section: Discussionsupporting
confidence: 58%
“…However, the same study (Kwon et al, 2001d) demonstrated that bee venom injected at the midline of the back is able to significantly reduce the same indicators of adjuvant-induced arthritis that develop after 12 days in the hind paw contralateral to adjuvant injection. Studies by other groups have also successfully inhibited signs of adjuvant-induced systemic polyarthritis with repeated bee venom injections at non-acupuncture points in the paws and on the back of rats (Chang and Bliven, 1979; Yiangou et al, 1993) indicating that injection at the acupuncture point is not critical to observe significant effects. Nonetheless, the same group has demonstrated that repeated bee venom injection (at acupuncture points) is anti-inflammatory in other rodent pain models including the prolonged type-II collagen-induced polyarthritis model (Lee et al, 2004).…”
Section: Anti-nociceptive and Anti-inflammatory Effects Of Bvtmentioning
confidence: 98%
“…Unfortunately, the time of sensory testing relative to the repeated bee venom injections in adjuvant-induced arthritic rodents was not reported (Kwon et al, 2001d, 2002) nor was the time of pain relief assessment in knee osteoarthritis (OA) patients, other than “at the end of the therapeutic period”, in the uncharacteristic report in which “OA symptoms completely disappeared after therapy” in 15 of 40 patients after 4 weeks of bee venom acupuncture twice each week (Kwon et al, 2001c). It is important to note that Chang and Bliven (1979) showed that a single injection of bee venom was most effective in inhibiting the development of paw swelling after subcutaneous adjuvant injection when administered the day prior, with decreasing effectiveness of a single bee venom injection out to 14 days post-adjuvant injection. Daily bee venom injection in arthritic rats initiated 16 days after adjuvant injection when adjuvant arthritis is established was effective in reducing paw inflammation for approximately seven days, after which paw swelling increased to the level of daily saline injected rats, despite continued daily bee venom injections (Chang and Bliven, 1979).…”
Section: Anti-nociceptive and Anti-inflammatory Effects Of Bvtmentioning
confidence: 99%
See 1 more Smart Citation
“…Cobra venom has been used to treat joint pain, inflammation, and arthritis in Indian traditional medicine, “Ayurveda” [4]. Bee venom has also been used to treat chronic inflammation (rheumatoid arthritis) and skin disease (acne and itch) and as pain relief for thousands of years [5, 6]. Recently, drugs derived from venom have been developed and are being used for treating patients suffering from various diseases [710].…”
Section: Introductionmentioning
confidence: 99%